2013
DOI: 10.1021/jp4058109
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Visible Light Photoactivity of Reduced Graphene Oxide/TiO2 by in Situ Hydrothermal Growth of Undergrown TiO2 with Graphene Oxide

Abstract: Graphene-related−TiO 2 (G−TiO 2 ) nanocomposites show enhanced photocatalytic performance, not only due to promoting photogenerated electrons migration but also by extending optical absorption to the visible light range. However, little is known about the origin of the visible light activity, which seems to depend much on the precursor of the titanium source. In this study, an efficient visible light active G− TiO 2 -413 was prepared by hydrothermally treating a graphene oxide (GO) suspension and TiO 2 sol wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(62 citation statements)
references
References 52 publications
5
56
0
1
Order By: Relevance
“…RGO shows peaks at 1718 cm -1 (C=O), 1577 cm -1 (skeletal vibration), 1399 cm -1 (C-OH), and 1246 cm -1 (C-O-C). 203 The TiO2 materials share a common broad peak at ~3400 cm -1 (-OH) associated with the adsorption of water. The…”
Section: Photocatalytic Performancementioning
confidence: 99%
“…RGO shows peaks at 1718 cm -1 (C=O), 1577 cm -1 (skeletal vibration), 1399 cm -1 (C-OH), and 1246 cm -1 (C-O-C). 203 The TiO2 materials share a common broad peak at ~3400 cm -1 (-OH) associated with the adsorption of water. The…”
Section: Photocatalytic Performancementioning
confidence: 99%
“…Williams et al [8] synthesized a hybrid rGO-TiO 2 material by irradiating a suspension containing TiO 2 nanoparticles and GO. The use of rGO was proposed by several groups for the preparation of highly photoactive composite materials based on titanium dioxide for the catalytic oxidation of aqueous organic pollutants [9][10][11][12][13][14], in order to exploit the high charge mobility of graphene and to maximize the photocatalytic efficiency by hindering the process of charge recombination.…”
Section: Introductionmentioning
confidence: 99%
“…The as-fabricated hybrid composites presented distinct advantages over the traditional methods in terms of the well-confined TiO 2 morphology and the formation of Ti-C bonds between TiO 2 nanoroads and rGO simultaneously. Long et al [180] used the hydrothermal method to prepare efficient visible light active GTiO 2 Ns by using a GO suspension and TiO 2 sol with undergrown TiO 2 nanoparticles at 413 K. The study of obtained materials demonstrated high chemical interaction at the interface of GO sheets and the polymeric Ti-O-Ti structure that facilitated the retaining of more alkoxyl groups; the induced crystal disorders and oxygen vacancies contributed positively to the performance of the obtained photocatalyst.…”
Section: Preparation Methods Of Gtio 2 Nsmentioning
confidence: 99%